Beef cattle lagoon seepage - Murphy, James P.; Harner, Joseph P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Most compacted soils can be used for lagoon liners to achieve seepage guidelines established by the Kansas Department of Health and Environment.
Keywords: Beef; Lagoon seepage; Permeability; Soil lagoon liner